Natural Succession After Fires at Secondary Forest in Fatuquero Village, Railaco District, Ermera Regency-Timor Leste - Bambang Hero Saharjo; Cornelio Gago (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2011)
Forest is unvaluable resourses which there in have biodiversity as germplas resources, forest product such as wood and non-wood, regulator of the water system, preventing flooding and erosion. Disruption of forest resources is still continues, even it’s increasing in a year to year. That damage caused by forest fires is one part of disruption are becoming more frequent. The negative impact caused by large fires is large enough to covering ecological damage, reduced biodiversity, reduced the economic value of forest and soil productivity, and also global climate change. This study aims to determine the development of natural succession after fires at secondary forest.